Clinical Significance of Increased Cardiac Troponin T in Patients with Chronic Hemodialysis and Cardiovascular Disease: Comparison to B-Type Natriuretic Peptide and A-Type Natriuretic Peptide Increase - Shinichiro Niizuma; Yoshitaka Iwanaga; Takehiko Washio; Tadashi Ashida; Shinsuke Harasawa; Shunichi Miyazaki; Naoya Matsumoto (Karger Publishers, 2019)
Background: An increased cardiac troponin T (cTnT) level identifies a high-risk group in patients with end-stage renal disease; however, the mechanism of cTnT elevation remains unclear in such patients without acute coronary syndrome (ACS). Therefore, we explored the relationship between cTnT levels and the hemodynamic parameters and the prognostic potential of cTnT in stable patients with chronic hemodialysis (HD). Methods: We included consecutive 174 patients with HD who were referred for coronary angiography due to stable coronary artery disease (CAD), peripheral artery disease (PAD), or heart failure (HF). Hemodynamic measurement was performed, and plasma cTnT, B-type natriuretic peptide (BNP), and A-type natriuretic peptide (ANP) were measured at the same time. The potential of 3 biomarkers to predict all-cause mortality, cardiac death or hospitalized HF, and vascular event was assessed. Results: Increased log cTnT levels were correlated with increased log BNP and log ANP levels (r = 0.531, p < 0.001 and r = 0.411, p < 0.001, respectively). Not increased log cTnT, but increased log BNP and log ANP were associated with the presence of CAD and the extent of CAD. In contrast, they were all associated with the New York Heart Association functional classification and the presence of PAD and significantly correlated with left ventricular end-diastolic pressure (LVEDP) in an independent manner. Increased cTnT and BNP levels were associated with the mortality and hospitalized HF. However, increased cTnT was not associated with vascular events, unlike increased BNP. Conclusions: In patients with chronic HD without ACS, increased cTnT reflected increased LVEDP and the presence of HF or PAD independently, and it did not reflect the presence of CAD in contrast to increased BNP. cTnT and BNP were significant prognostic predictors; however, increased cTnT was associated with HF-related events, not with arteriosclerotic events.